2008
DOI: 10.1152/ajpendo.00037.2008
|View full text |Cite
|
Sign up to set email alerts
|

Uteroplacental insufficiency and reducing litter size alters skeletal muscle mitochondrial biogenesis in a sex-specific manner in the adult rat

Abstract: Wadley GD, Siebel AL, Cooney GJ, McConell GK, Wlodek ME, Owens JA. Uteroplacental insufficiency and reducing litter size alters skeletal muscle mitochondrial biogenesis in a sex-specific manner in the adult rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
125
4
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(143 citation statements)
references
References 42 publications
12
125
4
2
Order By: Relevance
“…This observation was already made in skeletal muscle where mitochondrial metabolic characteristics and biogenesis were altered to a greater extent in male compared with female rats following in utero placental insufficiency (21,22,63). Moreover, long-term consequences of a maternal LP diet on glucose tolerance developed earlier in male than in female offspring (8,13).…”
Section: Discussionmentioning
confidence: 75%
“…This observation was already made in skeletal muscle where mitochondrial metabolic characteristics and biogenesis were altered to a greater extent in male compared with female rats following in utero placental insufficiency (21,22,63). Moreover, long-term consequences of a maternal LP diet on glucose tolerance developed earlier in male than in female offspring (8,13).…”
Section: Discussionmentioning
confidence: 75%
“…Since we have previously observed marked sex differences in a range of metabolic and cardiovascular outcomes in adult rats following uteroplacental insufficiency (20,29,31), it is possible there could be similar sex-specific effects on the expression of genes in the mitochondrial biogenesis pathway, GLUTs and antioxidant enzymes during cardiac development in growth restricted rats.…”
mentioning
confidence: 98%
“…Using well-established rodent models of uteroplacental insufficiency, our group, and others, have shown that growth restriction in prenatal and/or postnatal life adversely impacts on later metabolic and cardiovascular health in adulthood, including hypertension (27,31,32), cardiac hypertrophy (32), myocardial insulin resistance (26), impaired glucose tolerance (20), reduced cardiomyocyte number (5), and reduced expression of genes regulating mitochondrial biogenesis (synthesis) in skeletal muscle (29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both F1 male and female offspring have organ deficits, but only F1 male offspring develop hypertension and metabolic dysfunction in adult life (Wadley et al 2008, Moritz et al 2009). During late gestation, F1 female growth-restricted offspring become glucose intolerant, develop glomerular hypertrophy and have modifications in uterine artery function (Mazzuca et al 2010, Gallo et al 2012b.…”
Section: Introductionmentioning
confidence: 99%